2016
DOI: 10.17113/ftb.54.04.16.4248
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of apple aroma: A review

Abstract: SummaryFlavour is a key quality att ribute of apples defi ned by volatile aroma compounds. Biosynthesis of aroma compounds involves metabolic pathways in which the main precursors are fatt y and amino acids, and the main products are aldehydes, alcohols and esters. Some enzymes are crucial in the production of volatile compounds, such as lipoxygenase, alcohol dehydrogenase, and alcohol acyltransferase. Composition and concentration of volatiles in apples may be altered by pre-and postharvest factors that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 161 publications
5
142
1
Order By: Relevance
“…Among those compounds, benzaldehyde (6.568-18.508 mg/kg), 2-methylbutanol (2.301-13.421 mg/kg), butanol (0.643-5.247 mg/kg), (E) -2-hexenal (2.050-9.804 mg/kg), ethyl butanoate (1.914-6.906 mg/kg), ethyl 2-methylbutanoate (1.419-6.867 mg/kg) presented relatively higher amounts than other compounds. The results were agreed with other studies which found that esters, alcohols, aldehydes, ketones compounds could be considered as the main compounds to delicious apple (Espinodíaz et al, 2016). The OAV was considered as useful method to evaluate the contribution of aroma compound to whole aroma.…”
Section: Results and Conclusionsupporting
confidence: 92%
“…Among those compounds, benzaldehyde (6.568-18.508 mg/kg), 2-methylbutanol (2.301-13.421 mg/kg), butanol (0.643-5.247 mg/kg), (E) -2-hexenal (2.050-9.804 mg/kg), ethyl butanoate (1.914-6.906 mg/kg), ethyl 2-methylbutanoate (1.419-6.867 mg/kg) presented relatively higher amounts than other compounds. The results were agreed with other studies which found that esters, alcohols, aldehydes, ketones compounds could be considered as the main compounds to delicious apple (Espinodíaz et al, 2016). The OAV was considered as useful method to evaluate the contribution of aroma compound to whole aroma.…”
Section: Results and Conclusionsupporting
confidence: 92%
“…As listed in Table , 3 alcohols, 28 esters, and 2 terpenes were tentatively identified. Esters are generated by the esterification of alcohols and acyl‐CoA, and acyl alcohol transferase (AAT) is the key enzyme that transfers an acyl group to an alcohol (Bartley, Stoker, Martin, Hatfield, & Knee, ; Espino‐Díaz, Sepúlveda, González‐Aguilar, & Olivas, ). However, independent to the reaction of alcohols and esters, terpenoids including α‐farnesene and d ‐limonene are generated via mevalonate and deoxyxylulose phosphate pathways (Eisenreich, Bacher, Arigoni, & Rohdich, ; Sanz & Perez, ).…”
Section: Resultsmentioning
confidence: 99%
“…The type of esters generated from apples is dependent on the specificity of AAT enzyme to alcohols and acyl‐CoA (Echeverrıa, Graell, et al, ). Apples have AAT enzymes with various substrate‐specificity depending on their variety (Espino‐Díaz et al, ). It has been reported that exogenous HeOH and 2mBuOH in Fuji apples are converted to hexyl and 2‐methylbutyl acetate, respectively (Holland et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Hundreds of volatile compounds have been detected in the aroma profile of apples. These compounds are categorized as esters, alcohols, aldehydes, ketones and ethers [1,2]. Some of these compounds are labeled as "character impact," including trans-2-hexenal (green), hexanal (grassy, green), butyl acetate (red apple aroma), ethyl butanoate (fruity), butan-1-ol (sweet aroma), etc.…”
Section: Introductionmentioning
confidence: 99%